Multi-Objective Scheduling of Medical Personnel and Resources in Hospital Using Heuristic Approaches - Abdul Rahman, Syariza; Abdul Rahman, Rosshairy; Wibowo, Antoni; Negara, I Gede Putra Kusuma (UUM, 2022)
Scheduling problems in hospitals involved physicians, residents, nurses and resources. These scheduling have to fulfill a set of specific constraints. Conventional scheduling is usually a time-consuming process and uses manual approach. The previous developed scheduling however cannot be used directly in other hospitals since each hospital has different characteristics and complexities. In this research, a novel multi-objective scheduling model is proposed to overcome the limitations of the previous hospitals scheduling models. The proposed model involves medical personnel scheduling and optimizes the utility of resources in hospitals simultaneously to improve quality and efficiency in daily operations. Furthermore, several modifications of heuristic techniques are also developed to obtain the best scheduling in hospitals management.